Beyond water, beyond boundaries: spaces of water management in the Krishna River basin, South India - Venot, Jean-Philippe; Bharati, Luna; Giordano, Mark; Molle, Francois (Wiley, 2011)
As demand and competition for water resources increase, the river basin has become the primary unit for water management and planning. While appealing in principle, practical implementation of river basin management and allocation has often been problematic. This paper examines the case of the Krishna basin in South India. It highlights that conflicts over basin water are embedded in a broad reality of planning and development where multiple scales of decisionmaking and non-water issues are at play. While this defines the river basin as a disputed 'space of dependence', the river basin has yet to acquire a social reality. It is not yet a 'space of engagement' in and for which multiple actors take actions. This explains the endurance of an interstate dispute over the sharing of the Krishna waters and sets limits to what can be achieved through further basin water allocation and adjudication mechanisms - tribunals - that are too narrowly defined. There is a need to extend the domain of negotiation from that of a single river basin to multiple scales and to non-water sectors. Institutional arrangements for basin management need to internalise the political spaces of the Indian polity: the states and the panchayats. This re-scaling process is more likely to shape the river basin as a space of engagement in which partial agreements can be iteratively renegotiated, and constitute a promising alternative to the current interstate stalemate.